1967
DOI: 10.1017/s000748530005001x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and regulation of puparium formation in the larva of the tsetse fly Glossina morsitans orientalis Vanderplank in relation to humidity, light and mechanical stimuli

Abstract: From obsevations on larvae from laboratory-reared females of Glossina morsitans orientalis Vanderplank, six stages were recognised between the time of deposition (signalled in these experiments by a simple automatic device) and completion of puparium formation, each characterised by an associated pattern of behaviour. They are termed crawling (during which there is a stron phot-negative response), circling and reversing, head retraction, barrelling (the assumption of the puparial shape), hardening, and darkeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

1969
1969
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 13 publications
1
30
0
1
Order By: Relevance
“…These field puparia were selected from routine daily collections on the basis of pale colouration. Such puparia were assumed to be less than one hour old (FINLAYSON, 1967) at the commencement of incubation whereas the age of colony puparia tested was only known to be less than 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…These field puparia were selected from routine daily collections on the basis of pale colouration. Such puparia were assumed to be less than one hour old (FINLAYSON, 1967) at the commencement of incubation whereas the age of colony puparia tested was only known to be less than 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Clarke and Langley (1963) postulated a role for proprioceptive monitoring of crop distension in growth and molting of Locusta, and a similar control system has been suggested in the regulation of digestive enzyme activity in adult tsetse flies (Langley, 1966). Finlayson (1967) has recently demonstrated that mechanoreceptor input plays a role in the initiation of puparium formation in larvae of Glossina. The onset and termination of successive phases of insect molting and maturation is regulated by surface contact and body form in a number of studies cited by Cottrell (1964) and in certain of these, proprioceptive monitoring of body form is implicit.…”
Section: Discussionmentioning
confidence: 89%
“…A stage 3 larva (irreversible anterior retraction stage) looks similar to the stage 2 larva; however, it cannot lengthen itself when disturbed. Stage 4 larvae (barrelling stage, as in Finlayson's (1967) description) are oval. the same shape as normal pupae, with the mouthparts inverted, but with no visible tanning.…”
Section: Methodsmentioning
confidence: 99%